PENGARUH TERAPI KOMPLEMENTER OUKUP DAUN CENGKEH DAN BUAH PALA TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS - Rina Hariani; Utami, Risqi; Juni Ekasari, Dian (Universitas Batam, 2025)
ABSTRACT Approximately 72% of mothers who give birth normally experience perineal wounds, with 35% of them experiencing slow wound healing due to lack of optimal postpartum care. OUKUP therapy of clove leaves and nutmeg based on herbal steam is effective in accelerating the healing of perineal wounds naturally. This study aims to determine the effect of complementary therapy OUKUP clove leaves and nutmeg on perineal wound healing in postpartum mothers. The research method uses a quasi-experimental approach, with a pretest-posttest control group design. The population in this study were all postpartum mothers who experienced perineal wounds grade I-II. The number of samples consisted of 32 respondents, where the sample was divided into 2 so that it became 16 people for each group. The study shows that oukup therapy accelerates perineal wound healing (5 days) compared to the control (8 days), with a significant difference (p = 0.001). So it can be concluded that there is an effect of complementary therapy OUKUP clove leaves and nutmeg on perineal wound healing in postpartum mothers. Midwives are advised to consider implementing evidence-based complementary therapies and provide education on the use of clove and nutmeg leaf-based therapies. Keywords: OUKUP, Clove leaf, nutmeg, perineal wounds, postpartum